Prevalensi dan Derajat Infeksi Parasit Anisakis Sp. pada Ikan Tongkol Lisong ( Auxis Rochei) di Perairan Kota Ende - Venansius Jesmaryo Labhu; Diana A Wuri; Aji Winarso (Jurnal Veteriner Nusantara, 2022)
Tuna is often infected with endoparasites, one of which is the Anisakis sp. parasite. Anisakis sp. It is zoonotic, causing Anisakiasis in humans. In tuna, the parasite predilection of Anisakis sp. occurs in the digestive organs and muscles. The purpose of this study was to identify, as well as to determine the prevalence and degree of infection with the parasite Anisakis sp. on tuna in the waters of Ende Town. In this study, samples were taken from three markets in Ende Town, namely Mbonga Wani Market, Senggol Market and Wolowona Market. The sample of tuna that was taken was bullet tuna (Auxis rochei) with a total sample of 95 bullet tuna (Auxis rochei). From the results, it was shown that Anisakis sp. which infects bullet tuna (Auxis rochei) is the parasite Anisakis sp. type I. This is characterized by finding mucrons, boring teeth and ventriculus. In bullet tuna (Auxis rochei) the prevalence of Anisakis sp. is 26.31% and is included in the light category. On the prevalence of Anisakis sp. based on body length, bullet tuna (Auxis rochei) measuring 10cm – 20cm has a prevalence value of 10.52% while bullet tuna (Auxis rochei) measuring 20cm – 30cm has a prevalence of 36.84%. The value of the parasite infection degree Anisakis sp. on bullet tuna (Auxis rochei) is in the medium category with the infection degree value of 11.12.